Mercurial > hg > Gears > GearsAgda
view nat.agda @ 954:08281092430b
...
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Sun, 06 Oct 2024 17:59:51 +0900 |
parents | 057d3309ed9d |
children |
line wrap: on
line source
{-# OPTIONS --cubical-compatible --safe #-} module nat where open import Data.Nat open import Data.Nat.Properties open import Data.Empty open import Relation.Nullary open import Relation.Binary.PropositionalEquality open import Relation.Binary.Core open import Relation.Binary.Definitions open import logic open import Level hiding ( zero ; suc ) =→¬< : {x : ℕ } → ¬ ( x < x ) =→¬< {x} x<x with <-cmp x x ... | tri< a ¬b ¬c = ⊥-elim ( ¬b refl ) ... | tri≈ ¬a b ¬c = ⊥-elim ( ¬a x<x ) ... | tri> ¬a ¬b c = ⊥-elim ( ¬b refl ) >→¬< : {x y : ℕ } → (x < y ) → ¬ ( y < x ) >→¬< {x} {y} x<y y<x with <-cmp x y ... | tri< a ¬b ¬c = ⊥-elim ( ¬c y<x ) ... | tri≈ ¬a b ¬c = ⊥-elim ( ¬c y<x ) ... | tri> ¬a ¬b c = ⊥-elim ( ¬a x<y ) nat-<> : { x y : ℕ } → x < y → y < x → ⊥ nat-<> {x} {y} x<y y<x with <-cmp x y ... | tri< a ¬b ¬c = ⊥-elim ( ¬c y<x ) ... | tri≈ ¬a b ¬c = ⊥-elim ( ¬c y<x ) ... | tri> ¬a ¬b c = ⊥-elim ( ¬a x<y ) a<sa : {la : ℕ} → la < suc la a<sa {zero} = s≤s z≤n a<sa {suc la} = s≤s a<sa refl-≤s : {x : ℕ } → x ≤ suc x refl-≤s {zero} = z≤n refl-≤s {suc x} = s≤s (refl-≤s {x}) a≤sa : {x : ℕ } → x ≤ suc x a≤sa = refl-≤s nat-<≡ : { x : ℕ } → x < x → ⊥ nat-<≡ {x} x<x with <-cmp x x ... | tri< a ¬b ¬c = ⊥-elim ( ¬b refl ) ... | tri≈ ¬a b ¬c = ⊥-elim ( ¬a x<x ) ... | tri> ¬a ¬b c = ⊥-elim ( ¬a x<x ) nat-≡< : { x y : ℕ } → x ≡ y → x < y → ⊥ nat-≡< refl lt = nat-<≡ lt nat-≤> : { x y : ℕ } → x ≤ y → y < x → ⊥ nat-≤> {x} {y} x≤y y<x with <-cmp x y ... | tri< a ¬b ¬c = ⊥-elim ( ¬c y<x ) ... | tri≈ ¬a b ¬c = ⊥-elim ( ¬c y<x ) ... | tri> ¬a ¬b c = ⊥-elim (nat-<≡ (≤-trans c x≤y)) ≤-∨ : { x y : ℕ } → x ≤ y → ( (x ≡ y ) ∨ (x < y) ) ≤-∨ {x} {y} x≤y with <-cmp x y ... | tri< a ¬b ¬c = case2 a ... | tri≈ ¬a b ¬c = case1 b ... | tri> ¬a ¬b c = ⊥-elim ( nat-<≡ (≤-trans c x≤y)) <-∨ : { x y : ℕ } → x < suc y → ( (x ≡ y ) ∨ (x < y) ) <-∨ {x} {y} x<sy with <-cmp x y ... | tri< a ¬b ¬c = case2 a ... | tri≈ ¬a b ¬c = case1 b ... | tri> ¬a ¬b c = ⊥-elim ( nat-<≡ (≤-trans x<sy c )) ¬a≤a : {la : ℕ} → suc la ≤ la → ⊥ ¬a≤a {x} sx≤x = ⊥-elim ( nat-≤> sx≤x a<sa ) max : (x y : ℕ) → ℕ max zero zero = zero max zero (suc x) = (suc x) max (suc x) zero = (suc x) max (suc x) (suc y) = suc ( max x y ) x≤max : (x y : ℕ) → x ≤ max x y x≤max zero zero = ≤-refl x≤max zero (suc x) = z≤n x≤max (suc x) zero = ≤-refl x≤max (suc x) (suc y) = s≤s( x≤max x y ) y≤max : (x y : ℕ) → y ≤ max x y y≤max zero zero = ≤-refl y≤max zero (suc x) = ≤-refl y≤max (suc x) zero = z≤n y≤max (suc x) (suc y) = s≤s( y≤max x y ) x≤y→max=y : (x y : ℕ) → x ≤ y → max x y ≡ y x≤y→max=y zero zero x≤y = refl x≤y→max=y zero (suc y) x≤y = refl x≤y→max=y (suc x) (suc y) lt with <-cmp x y ... | tri< a ¬b ¬c = cong suc (x≤y→max=y x y (≤-trans a≤sa a)) ... | tri≈ ¬a refl ¬c = cong suc (x≤y→max=y x y ≤-refl ) ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> c lt ) y≤x→max=x : (x y : ℕ) → y ≤ x → max x y ≡ x y≤x→max=x zero zero y≤x = refl y≤x→max=x zero (suc y) () y≤x→max=x (suc x) zero lt = refl y≤x→max=x (suc x) (suc y) lt with <-cmp y x ... | tri< a ¬b ¬c = cong suc (y≤x→max=x x y (≤-trans a≤sa a)) ... | tri≈ ¬a refl ¬c = cong suc (y≤x→max=x x y ≤-refl ) ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> c lt ) -- _*_ : ℕ → ℕ → ℕ -- _*_ zero _ = zero -- _*_ (suc n) m = m + ( n * m ) -- x ^ y exp : ℕ → ℕ → ℕ exp _ zero = 1 exp n (suc m) = n * ( exp n m ) div2 : ℕ → (ℕ ∧ Bool ) div2 zero = ⟪ 0 , false ⟫ div2 (suc zero) = ⟪ 0 , true ⟫ div2 (suc (suc n)) = ⟪ suc (proj1 (div2 n)) , proj2 (div2 n) ⟫ where open _∧_ div2-rev : (ℕ ∧ Bool ) → ℕ div2-rev ⟪ x , true ⟫ = suc (x + x) div2-rev ⟪ x , false ⟫ = x + x div2-eq : (x : ℕ ) → div2-rev ( div2 x ) ≡ x div2-eq zero = refl div2-eq (suc zero) = refl div2-eq (suc (suc x)) with div2 x in eq1 ... | ⟪ x1 , true ⟫ = begin -- eq1 : div2 x ≡ ⟪ x1 , true ⟫ div2-rev ⟪ suc x1 , true ⟫ ≡⟨⟩ suc (suc (x1 + suc x1)) ≡⟨ cong (λ k → suc (suc k )) (+-comm x1 _ ) ⟩ suc (suc (suc (x1 + x1))) ≡⟨⟩ suc (suc (div2-rev ⟪ x1 , true ⟫)) ≡⟨ cong (λ k → suc (suc (div2-rev k ))) (sym eq1) ⟩ suc (suc (div2-rev (div2 x))) ≡⟨ cong (λ k → suc (suc k)) (div2-eq x) ⟩ suc (suc x) ∎ where open ≡-Reasoning ... | ⟪ x1 , false ⟫ = begin div2-rev ⟪ suc x1 , false ⟫ ≡⟨⟩ suc (x1 + suc x1) ≡⟨ cong (λ k → (suc k )) (+-comm x1 _ ) ⟩ suc (suc (x1 + x1)) ≡⟨⟩ suc (suc (div2-rev ⟪ x1 , false ⟫)) ≡⟨ cong (λ k → suc (suc (div2-rev k ))) (sym eq1) ⟩ suc (suc (div2-rev (div2 x))) ≡⟨ cong (λ k → suc (suc k)) (div2-eq x) ⟩ suc (suc x) ∎ where open ≡-Reasoning sucprd : {i : ℕ } → 0 < i → suc (pred i) ≡ i sucprd {suc i} 0<i = refl 0<s : {x : ℕ } → zero < suc x 0<s {_} = s≤s z≤n px<py : {x y : ℕ } → pred x < pred y → x < y px<py {zero} {suc y} lt = 0<s px<py {suc x} {suc y} lt with <-cmp x y ... | tri< a ¬b ¬c = s≤s a ... | tri≈ ¬a b ¬c = ⊥-elim ( nat-≡< b lt ) ... | tri> ¬a ¬b c = ⊥-elim ( nat-<> c lt ) minus : (a b : ℕ ) → ℕ minus a zero = a minus zero (suc b) = zero minus (suc a) (suc b) = minus a b _-_ = minus sn-m=sn-m : {m n : ℕ } → m ≤ n → suc n - m ≡ suc ( n - m ) sn-m=sn-m {0} {n} m≤n = refl sn-m=sn-m {suc m} {suc n} le with <-cmp m n ... | tri< a ¬b ¬c = sm00 where sm00 : suc n - m ≡ suc ( n - m ) sm00 = sn-m=sn-m {m} {n} (≤-trans a≤sa a ) ... | tri≈ ¬a refl ¬c = sn-m=sn-m {m} {n} ≤-refl ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> c le ) si-sn=i-n : {i n : ℕ } → n < i → suc (i - suc n) ≡ (i - n) si-sn=i-n {i} {n} n<i = begin suc (i - suc n) ≡⟨ sym (sn-m=sn-m n<i ) ⟩ suc i - suc n ≡⟨⟩ i - n ∎ where open ≡-Reasoning n-m<n : (n m : ℕ ) → n - m ≤ n n-m<n zero zero = z≤n n-m<n (suc n) zero = s≤s (n-m<n n zero) n-m<n zero (suc m) = z≤n n-m<n (suc n) (suc m) = ≤-trans (n-m<n n m ) refl-≤s m-0=m : {m : ℕ } → m - zero ≡ m m-0=m {zero} = refl m-0=m {suc m} = cong suc (m-0=m {m}) m-m=0 : {m : ℕ } → m - m ≡ zero m-m=0 {zero} = refl m-m=0 {suc m} = m-m=0 {m} refl-≤ : {x : ℕ } → x ≤ x refl-≤ {zero} = z≤n refl-≤ {suc x} = s≤s (refl-≤ {x}) refl-≤≡ : {x y : ℕ } → x ≡ y → x ≤ y refl-≤≡ refl = refl-≤ px≤x : {x : ℕ } → pred x ≤ x px≤x {zero} = refl-≤ px≤x {suc x} = refl-≤s px≤py : {x y : ℕ } → x ≤ y → pred x ≤ pred y px≤py {zero} {zero} x≤y = refl-≤ px≤py {suc x} {zero} () px≤py {zero} {suc y} le = z≤n px≤py {suc x} {suc y} x≤y with <-cmp x y ... | tri< a ¬b ¬c = ≤-trans a≤sa a ... | tri≈ ¬a b ¬c = refl-≤≡ b ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> c x≤y ) n-n-m=m : {m n : ℕ } → m ≤ n → m ≡ (n - (n - m)) n-n-m=m {0} {zero} le = refl n-n-m=m {0} {suc n} lt = begin 0 ≡⟨ sym (m-m=0 {suc n}) ⟩ suc n - suc n ∎ where open ≡-Reasoning n-n-m=m {suc m} {suc n} le = begin suc m ≡⟨ cong suc ( n-n-m=m (px≤py le)) ⟩ suc (n - (n - m)) ≡⟨ sym (sn-m=sn-m (n-m<n n m)) ⟩ suc n - (n - m) ∎ where open ≡-Reasoning m+= : {i j m : ℕ } → m + i ≡ m + j → i ≡ j m+= {i} {j} {zero} refl = refl m+= {i} {j} {suc m} eq = m+= {i} {j} {m} ( cong (λ k → pred k ) eq ) +m= : {i j m : ℕ } → i + m ≡ j + m → i ≡ j +m= {i} {j} {m} eq = m+= ( subst₂ (λ j k → j ≡ k ) (+-comm i _ ) (+-comm j _ ) eq ) less-1 : { n m : ℕ } → suc n < m → n < m less-1 sn<m = <-trans a<sa sn<m sa=b→a<b : { n m : ℕ } → suc n ≡ m → n < m sa=b→a<b {n} {m} sn=m = subst (λ k → n < k ) sn=m a<sa minus+n : {x y : ℕ } → suc x > y → minus x y + y ≡ x minus+n {x} {zero} _ = trans (sym (+-comm zero _ )) refl minus+n {zero} {suc y} lt = ⊥-elim ( nat-≤> lt (≤-trans a<sa (s≤s (s≤s z≤n)) )) minus+n {suc x} {suc y} y<sx with <-cmp y (suc x) ... | tri< a ¬b ¬c = begin minus (suc x) (suc y) + suc y ≡⟨ +-comm _ (suc y) ⟩ suc y + minus x y ≡⟨ cong ( λ k → suc k ) ( begin y + minus x y ≡⟨ +-comm y _ ⟩ minus x y + y ≡⟨ minus+n {x} {y} a ⟩ x ∎ ) ⟩ suc x ∎ where open ≡-Reasoning ... | tri≈ ¬a b ¬c = ⊥-elim ( nat-≡< b (px≤py y<sx )) ... | tri> ¬a ¬b c = ⊥-elim ( nat-<> c (px≤py y<sx )) +<-cong : {x y z : ℕ } → x < y → z + x < z + y +<-cong {x} {y} {zero} x<y = x<y +<-cong {x} {y} {suc z} x<y = s≤s (+<-cong {x} {y} {z} x<y) <-minus-0 : {x y z : ℕ } → z + x < z + y → x < y <-minus-0 {x} {y} {z} x<y with <-cmp x y ... | tri< a ¬b ¬c = a ... | tri≈ ¬a b ¬c = ⊥-elim ( nat-≡< (cong (λ k → z + k ) b) x<y ) ... | tri> ¬a ¬b c = ⊥-elim ( nat-<> x<y (+<-cong {y} {x} {z} c)) <-minus : {x y z : ℕ } → x + z < y + z → x < y <-minus {x} {y} {z} lt = <-minus-0 ( subst₂ ( λ j k → j < k ) (+-comm x _) (+-comm y _ ) lt ) x≤x+y : {z y : ℕ } → z ≤ z + y x≤x+y {zero} {y} = z≤n x≤x+y {suc z} {y} = s≤s (x≤x+y {z} {y}) x≤y+x : {z y : ℕ } → z ≤ y + z x≤y+x {z} {y} = subst (λ k → z ≤ k ) (+-comm _ y ) x≤x+y x≤x+sy : {x y : ℕ} → x < x + suc y x≤x+sy {x} {y} = begin suc x ≤⟨ x≤x+y ⟩ suc x + y ≡⟨ cong (λ k → k + y) (+-comm 1 x ) ⟩ (x + 1) + y ≡⟨ (+-assoc x 1 _) ⟩ x + suc y ∎ where open ≤-Reasoning <-plus-0 : {x y z : ℕ } → x < y → z + x < z + y <-plus-0 = +<-cong <-plus : {x y z : ℕ } → x < y → x + z < y + z <-plus {x} {y} {z} x<y = subst₂ (λ j k → j < k ) (+-comm z x ) (+-comm z y ) ( <-plus-0 x<y ) ≤-plus-0 : {x y z : ℕ } → x ≤ y → z + x ≤ z + y ≤-plus-0 {x} {y} {zero} lt = lt ≤-plus-0 {x} {y} {suc z} lt = s≤s ( ≤-plus-0 {x} {y} {z} lt ) ≤-plus : {x y z : ℕ } → x ≤ y → x + z ≤ y + z ≤-plus {x} {y} {z} x≤y = subst₂ (λ j k → j ≤ k ) (+-comm z x ) (+-comm z y ) ( ≤-plus-0 x≤y ) x+y<z→x<z : {x y z : ℕ } → x + y < z → x < z x+y<z→x<z {x} {zero} {z} xy<z = subst (λ k → k < z ) (+-comm x zero ) xy<z x+y<z→x<z {x} {suc y} {z} xy<z = <-minus {x} {z} {suc y} (<-trans xy<z x≤x+sy ) *≤ : {x y z : ℕ } → x ≤ y → x * z ≤ y * z *≤ lt = *-mono-≤ lt ≤-refl <to≤ : {x y : ℕ } → x < y → x ≤ y <to≤ {x} {y} x<y with <-cmp x (suc y) ... | tri< a ¬b ¬c = px≤py a ... | tri≈ ¬a b ¬c = ⊥-elim ( nat-≡< b (≤-trans x<y a≤sa )) ... | tri> ¬a ¬b c = ⊥-elim ( nat-<> c (≤-trans x<y a≤sa )) <sto≤ : {x y : ℕ } → x < suc y → x ≤ y <sto≤ {x} {y} x<sy with <-cmp x y ... | tri< a ¬b ¬c = <to≤ a ... | tri≈ ¬a refl ¬c = ≤-refl ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> c x<sy ) *< : {x y z : ℕ } → x < y → x * suc z < y * suc z *< {x} {zero} {z} () *< {x} {suc y} {z} x<y = s≤s ( begin x * suc z ≤⟨ lem01 ⟩ y * suc z ≤⟨ x≤x+y ⟩ y * suc z + z ≡⟨ +-comm _ z ⟩ z + y * suc z ∎ ) where open ≤-Reasoning lem01 : x * suc z ≤ y * suc z lem01 = *-mono-≤ {x} {y} {suc z} (<sto≤ x<y) ≤-refl <to<s : {x y : ℕ } → x < y → x < suc y <to<s x<y = <-trans x<y a<sa <tos<s : {x y : ℕ } → x < y → suc x < suc y <tos<s x<y = s≤s x<y <∨≤ : ( x y : ℕ ) → (x < y ) ∨ (y ≤ x) <∨≤ x y with <-cmp x y ... | tri< a ¬b ¬c = case1 a ... | tri≈ ¬a refl ¬c = case2 ≤-refl ... | tri> ¬a ¬b c = case2 (<to≤ c) x<y→≤ : {x y : ℕ } → x < y → x ≤ suc y x<y→≤ {x} {y} x<y with <-cmp x (suc y) ... | tri< a ¬b ¬c = <to≤ a ... | tri≈ ¬a b ¬c = refl-≤≡ b ... | tri> ¬a ¬b c = ⊥-elim ( ¬a ( ≤-trans x<y a≤sa )) ≤→= : {i j : ℕ} → i ≤ j → j ≤ i → i ≡ j ≤→= {i} {j} i≤j j≤i with <-cmp i j ... | tri< a ¬b ¬c = ⊥-elim ( nat-≤> j≤i a ) ... | tri≈ ¬a b ¬c = b ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> i≤j c ) sx≤py→x≤y : {x y : ℕ } → suc x ≤ suc y → x ≤ y sx≤py→x≤y = px≤py sx<py→x<y : {x y : ℕ } → suc x < suc y → x < y sx<py→x<y {x} {y} sx<sy with <-cmp x y ... | tri< a ¬b ¬c = a ... | tri≈ ¬a b ¬c = ⊥-elim ( nat-≡< (cong suc b) sx<sy ) ... | tri> ¬a ¬b c = ⊥-elim ( nat-<> (s≤s c) sx<sy ) sx≤y→x≤y : {x y : ℕ } → suc x ≤ y → x ≤ y sx≤y→x≤y sx≤y = ≤-trans a≤sa sx≤y x<sy→x≤y : {x y : ℕ } → x < suc y → x ≤ y x<sy→x≤y = <sto≤ x≤y→x<sy : {x y : ℕ } → x ≤ y → x < suc y x≤y→x<sy {.zero} {y} z≤n = ≤-trans a<sa (s≤s z≤n) x≤y→x<sy {.(suc _)} {.(suc _)} (s≤s le) = s≤s ( x≤y→x<sy le) sx≤y→x<y : {x y : ℕ } → suc x ≤ y → x < y sx≤y→x<y sx≤y = sx≤y open import Data.Product i-j=0→i=j : {i j : ℕ } → j ≤ i → i - j ≡ 0 → i ≡ j i-j=0→i=j {i} {j} le j=0 = begin i ≡⟨ sym (m-0=m) ⟩ i - 0 ≡⟨ cong (λ k → i - k ) (sym j=0) ⟩ i - (i - j ) ≡⟨ sym (n-n-m=m le) ⟩ j ∎ where open ≡-Reasoning m*n=0⇒m=0∨n=0 : {i j : ℕ} → i * j ≡ 0 → (i ≡ 0) ∨ ( j ≡ 0 ) m*n=0⇒m=0∨n=0 {zero} {j} eq = case1 refl m*n=0⇒m=0∨n=0 {suc i} {zero} eq = case2 refl minus+1 : {x y : ℕ } → y ≤ x → suc (minus x y) ≡ minus (suc x) y minus+1 {zero} {zero} y≤x = refl minus+1 {suc x} {zero} y≤x = refl minus+1 {suc x} {suc y} y≤x = minus+1 {x} {y} (sx≤py→x≤y y≤x) minus+yz : {x y z : ℕ } → z ≤ y → x + minus y z ≡ minus (x + y) z minus+yz {zero} {y} {z} _ = refl minus+yz {suc x} {y} {z} z≤y = begin suc x + minus y z ≡⟨ cong suc ( minus+yz z≤y ) ⟩ suc (minus (x + y) z) ≡⟨ minus+1 {x + y} {z} (≤-trans z≤y (subst (λ g → y ≤ g) (+-comm y x) x≤x+y) ) ⟩ minus (suc x + y) z ∎ where open ≡-Reasoning minus<=0 : {x y : ℕ } → x ≤ y → minus x y ≡ 0 minus<=0 {0} {zero} le = refl minus<=0 {0} {suc y} le = refl minus<=0 {suc x} {suc y} le = minus<=0 {x} {y} (sx≤py→x≤y le) minus>0 : {x y : ℕ } → x < y → 0 < minus y x minus>0 {zero} {suc _} lt = lt minus>0 {suc x} {suc y} lt = minus>0 {x} {y} (sx<py→x<y lt) minus>0→x<y : {x y : ℕ } → 0 < minus y x → x < y minus>0→x<y {x} {y} lt with <-cmp x y ... | tri< a ¬b ¬c = a ... | tri≈ ¬a refl ¬c = ⊥-elim ( nat-≡< (sym (minus<=0 {x} ≤-refl)) lt ) ... | tri> ¬a ¬b c = ⊥-elim ( nat-≡< (sym (minus<=0 {y} (≤-trans refl-≤s c ))) lt ) minus+y-y : {x y : ℕ } → (x + y) - y ≡ x minus+y-y {zero} {y} = minus<=0 {zero + y} {y} ≤-refl minus+y-y {suc x} {y} = begin (suc x + y) - y ≡⟨ sym (minus+1 {_} {y} x≤y+x) ⟩ suc ((x + y) - y) ≡⟨ cong suc (minus+y-y {x} {y}) ⟩ suc x ∎ where open ≡-Reasoning minus+yx-yz : {x y z : ℕ } → (y + x) - (y + z) ≡ x - z minus+yx-yz {x} {zero} {z} = refl minus+yx-yz {x} {suc y} {z} = minus+yx-yz {x} {y} {z} minus+xy-zy : {x y z : ℕ } → (x + y) - (z + y) ≡ x - z minus+xy-zy {x} {y} {z} = subst₂ (λ j k → j - k ≡ x - z ) (+-comm y x) (+-comm y z) (minus+yx-yz {x} {y} {z}) +cancel<l : (x z : ℕ ) {y : ℕ} → y + x < y + z → x < z +cancel<l x z {zero} lt = lt +cancel<l x z {suc y} lt = +cancel<l x z {y} (sx<py→x<y lt) +cancel<r : (x z : ℕ ) {y : ℕ} → x + y < z + y → x < z +cancel<r x z {y} lt = +cancel<l x z (subst₂ (λ j k → j < k ) (+-comm x _) (+-comm z _) lt ) minus<z : {x y z : ℕ } → x < y → z ≤ x → x - z < y - z minus<z {x} {y} {z} x<y z≤x = +cancel<r _ _ ( begin suc ( (x - z) + z ) ≡⟨ cong suc (minus+n (s≤s z≤x) ) ⟩ suc x ≤⟨ x<y ⟩ y ≡⟨ sym ( minus+n (<-trans (s≤s z≤x) (s≤s x<y) )) ⟩ (y - z ) + z ∎ ) where open ≤-Reasoning y-x<y : {x y : ℕ } → 0 < x → 0 < y → y - x < y y-x<y {x} {y} 0<x 0<y with <-cmp x (suc y) ... | tri< a ¬b ¬c = +cancel<r (y - x) _ ( begin suc ((y - x) + x) ≡⟨ cong suc (minus+n {y} {x} a ) ⟩ suc y ≡⟨ +-comm 1 _ ⟩ y + suc 0 ≤⟨ +-mono-≤ ≤-refl 0<x ⟩ y + x ∎ ) where open ≤-Reasoning ... | tri≈ ¬a refl ¬c = subst ( λ k → k < y ) (sym (minus<=0 {y} {x} refl-≤s )) 0<y ... | tri> ¬a ¬b c = subst ( λ k → k < y ) (sym (minus<=0 {y} {x} (≤-trans (≤-trans refl-≤s refl-≤s) c))) 0<y -- suc (suc y) ≤ x → y ≤ x open import Relation.Binary.Definitions distr-minus-* : {x y z : ℕ } → (minus x y) * z ≡ minus (x * z) (y * z) distr-minus-* {x} {zero} {z} = refl distr-minus-* {x} {suc y} {z} with <-cmp x y distr-minus-* {x} {suc y} {z} | tri< a ¬b ¬c = begin minus x (suc y) * z ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} (x<y→≤ a)) ⟩ 0 * z ≡⟨ sym (minus<=0 {x * z} {z + y * z} le ) ⟩ minus (x * z) (z + y * z) ∎ where open ≡-Reasoning le : x * z ≤ z + y * z le = ≤-trans lemma (subst (λ k → y * z ≤ k ) (+-comm _ z ) (x≤x+y {y * z} {z} ) ) where lemma : x * z ≤ y * z lemma = *≤ {x} {y} {z} (<to≤ a) distr-minus-* {x} {suc y} {z} | tri≈ ¬a refl ¬c = begin minus x (suc y) * z ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} refl-≤s ) ⟩ 0 * z ≡⟨ sym (minus<=0 {x * z} {z + y * z} (lt {x} {z} )) ⟩ minus (x * z) (z + y * z) ∎ where open ≡-Reasoning lt : {x z : ℕ } → x * z ≤ z + x * z lt {zero} {zero} = z≤n lt {suc x} {zero} = lt {x} {zero} lt {x} {suc z} = ≤-trans lemma refl-≤s where lemma : x * suc z ≤ z + x * suc z lemma = subst (λ k → x * suc z ≤ k ) (+-comm _ z) (x≤x+y {x * suc z} {z}) distr-minus-* {x} {suc y} {z} | tri> ¬a ¬b c = +m= {_} {_} {suc y * z} ( begin minus x (suc y) * z + suc y * z ≡⟨ sym (proj₂ *-distrib-+ z (minus x (suc y) ) _) ⟩ ( minus x (suc y) + suc y ) * z ≡⟨ cong (λ k → k * z) (minus+n {x} {suc y} (s≤s c)) ⟩ x * z ≡⟨ sym (minus+n {x * z} {suc y * z} (s≤s (lt c))) ⟩ minus (x * z) (suc y * z) + suc y * z ∎ ) where open ≡-Reasoning lt : {x y z : ℕ } → suc y ≤ x → z + y * z ≤ x * z lt {x} {y} {z} le = *≤ le distr-minus-*' : {z x y : ℕ } → z * (minus x y) ≡ minus (z * x) (z * y) distr-minus-*' {z} {x} {y} = begin z * (minus x y) ≡⟨ *-comm _ (x - y) ⟩ (minus x y) * z ≡⟨ distr-minus-* {x} {y} {z} ⟩ minus (x * z) (y * z) ≡⟨ cong₂ (λ j k → j - k ) (*-comm x z ) (*-comm y z) ⟩ minus (z * x) (z * y) ∎ where open ≡-Reasoning minus- : {x y z : ℕ } → suc x > z + y → minus (minus x y) z ≡ minus x (y + z) minus- {x} {y} {z} gt = +m= {_} {_} {z} ( begin minus (minus x y) z + z ≡⟨ minus+n {_} {z} lemma ⟩ minus x y ≡⟨ +m= {_} {_} {y} ( begin minus x y + y ≡⟨ minus+n {_} {y} lemma1 ⟩ x ≡⟨ sym ( minus+n {_} {z + y} gt ) ⟩ minus x (z + y) + (z + y) ≡⟨ sym ( +-assoc (minus x (z + y)) _ _ ) ⟩ minus x (z + y) + z + y ∎ ) ⟩ minus x (z + y) + z ≡⟨ cong (λ k → minus x k + z ) (+-comm _ y ) ⟩ minus x (y + z) + z ∎ ) where open ≡-Reasoning lemma1 : suc x > y lemma1 = x+y<z→x<z (subst (λ k → k < suc x ) (+-comm z _ ) gt ) lemma : suc (minus x y) > z lemma = <-minus {_} {_} {y} ( subst ( λ x → z + y < suc x ) (sym (minus+n {x} {y} lemma1 )) gt ) sn≤1→n=0 : {n : ℕ } → suc n ≤ 1 → n ≡ 0 sn≤1→n=0 {n} sn≤1 with <-cmp n 0 ... | tri≈ ¬a b ¬c = b ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> c sn≤1 ) minus-* : {M k n : ℕ } → n < k → minus k (suc n) * M ≡ minus (minus k n * M ) M minus-* {zero} {k} {n} lt = begin minus k (suc n) * zero ≡⟨ *-comm (minus k (suc n)) zero ⟩ zero * minus k (suc n) ≡⟨⟩ 0 * minus k n ≡⟨ *-comm 0 (minus k n) ⟩ minus (minus k n * 0 ) 0 ∎ where open ≡-Reasoning minus-* {suc m} {k} {n} lt with <-cmp k 1 minus-* {suc m} {k} {n} lt | tri< a ¬b ¬c = ⊥-elim ( nat-≤> (sx≤py→x≤y a) (≤-trans (s≤s z≤n) lt) ) minus-* {suc m} {k} {n} lt | tri≈ ¬a refl ¬c = subst (λ k → minus 0 k * suc m ≡ minus (minus 1 k * suc m) (suc m)) (sym n=0) lem where n=0 : n ≡ 0 n=0 = sn≤1→n=0 lt lem : minus 0 0 * suc m ≡ minus (minus 1 0 * suc m) (suc m) lem = begin minus 0 0 * suc m ≡⟨⟩ 0 ≡⟨ sym ( minus<=0 {suc m} {suc m} ≤-refl ) ⟩ minus (suc m) (suc m) ≡⟨ cong (λ k → minus k (suc m)) (+-comm 0 (suc m) ) ⟩ minus (suc m + 0) (suc m) ≡⟨⟩ minus (minus 1 0 * suc m) (suc m) ∎ where open ≡-Reasoning minus-* {suc m} {k} {n} lt | tri> ¬a ¬b c = begin minus k (suc n) * M ≡⟨ distr-minus-* {k} {suc n} {M} ⟩ minus (k * M ) ((suc n) * M) ≡⟨⟩ minus (k * M ) (M + n * M ) ≡⟨ cong (λ x → minus (k * M) x) (+-comm M _ ) ⟩ minus (k * M ) ((n * M) + M ) ≡⟨ sym ( minus- {k * M} {n * M} (lemma lt) ) ⟩ minus (minus (k * M ) (n * M)) M ≡⟨ cong (λ x → minus x M ) ( sym ( distr-minus-* {k} {n} )) ⟩ minus (minus k n * M ) M ∎ where M = suc m lemma : {n k m : ℕ } → n < k → suc (k * suc m) > suc m + n * suc m lemma {n} {k} {m} lt = ≤-plus-0 {_} {_} {1} (*≤ lt ) open ≡-Reasoning x=y+z→x-z=y : {x y z : ℕ } → x ≡ y + z → x - z ≡ y x=y+z→x-z=y {x} {zero} {.x} refl = minus<=0 {x} {x} refl-≤ -- x ≡ suc (y + z) → (x ≡ y + z → x - z ≡ y) → (x - z) ≡ suc y x=y+z→x-z=y {suc x} {suc y} {zero} eq = begin -- suc x ≡ suc (y + zero) → (suc x - zero) ≡ suc y suc x - zero ≡⟨ refl ⟩ suc x ≡⟨ eq ⟩ suc y + zero ≡⟨ +-comm _ zero ⟩ suc y ∎ where open ≡-Reasoning x=y+z→x-z=y {suc x} {suc y} {suc z} eq = x=y+z→x-z=y {x} {suc y} {z} ( begin x ≡⟨ cong pred eq ⟩ pred (suc y + suc z) ≡⟨ +-comm _ (suc z) ⟩ suc z + y ≡⟨ cong suc ( +-comm _ y ) ⟩ suc y + z ∎ ) where open ≡-Reasoning m*1=m : {m : ℕ } → m * 1 ≡ m m*1=m {zero} = refl m*1=m {suc m} = cong suc m*1=m +-cancel-1 : (x y z : ℕ ) → x + y ≡ x + z → y ≡ z +-cancel-1 zero y z eq = eq +-cancel-1 (suc x) y z eq = +-cancel-1 x y z (cong pred eq ) +-cancel-0 : (x y z : ℕ ) → y + x ≡ z + x → y ≡ z +-cancel-0 x y z eq = +-cancel-1 x y z (trans (+-comm x y) (trans eq (sym (+-comm x z)) )) *-cancel-left : {x y z : ℕ } → x > 0 → x * y ≡ x * z → y ≡ z *-cancel-left {suc x} {zero} {zero} lt eq = refl *-cancel-left {suc x} {zero} {suc z} lt eq = ⊥-elim ( nat-≡< eq (s≤s (begin x * zero ≡⟨ *-comm x _ ⟩ zero ≤⟨ z≤n ⟩ z + x * suc z ∎ ))) where open ≤-Reasoning *-cancel-left {suc x} {suc y} {zero} lt eq = ⊥-elim ( nat-≡< (sym eq) (s≤s (begin x * zero ≡⟨ *-comm x _ ⟩ zero ≤⟨ z≤n ⟩ _ ∎ ))) where open ≤-Reasoning *-cancel-left {suc x} {suc y} {suc z} lt eq with cong pred eq ... | eq1 = cong suc (*-cancel-left {suc x} {y} {z} lt (+-cancel-0 x _ _ (begin y + x * y + x ≡⟨ +-assoc y _ _ ⟩ y + (x * y + x) ≡⟨ cong (λ k → y + (k + x)) (*-comm x _) ⟩ y + (y * x + x) ≡⟨ cong (_+_ y) (+-comm _ x) ⟩ y + (x + y * x ) ≡⟨ refl ⟩ y + suc y * x ≡⟨ cong (_+_ y) (*-comm (suc y) _) ⟩ y + x * suc y ≡⟨ eq1 ⟩ z + x * suc z ≡⟨ refl ⟩ _ ≡⟨ sym ( cong (_+_ z) (*-comm (suc z) _) ) ⟩ _ ≡⟨ sym ( cong (_+_ z) (+-comm _ x)) ⟩ z + (z * x + x) ≡⟨ sym ( cong (λ k → z + (k + x)) (*-comm x _) ) ⟩ z + (x * z + x) ≡⟨ sym ( +-assoc z _ _) ⟩ z + x * z + x ∎ ))) where open ≡-Reasoning record Finduction {n m : Level} (P : Set n ) (Q : P → Set m ) (f : P → ℕ) : Set (n Level.⊔ m) where field fzero : {p : P} → f p ≡ zero → Q p pnext : (p : P ) → P decline : {p : P} → 0 < f p → f (pnext p) < f p ind : {p : P} → Q (pnext p) → Q p y<sx→y≤x : {x y : ℕ} → y < suc x → y ≤ x y<sx→y≤x = x<sy→x≤y fi0 : (x : ℕ) → x ≤ zero → x ≡ zero fi0 .0 z≤n = refl f-induction : {n m : Level} {P : Set n } → {Q : P → Set m } → (f : P → ℕ) → Finduction P Q f → (p : P ) → Q p f-induction {n} {m} {P} {Q} f I p with <-cmp 0 (f p) ... | tri> ¬a ¬b () ... | tri≈ ¬a b ¬c = Finduction.fzero I (sym b) ... | tri< lt _ _ = f-induction0 p (f p) (<to≤ (Finduction.decline I lt)) where f-induction0 : (p : P) → (x : ℕ) → (f (Finduction.pnext I p)) ≤ x → Q p f-induction0 p zero le = Finduction.ind I (Finduction.fzero I (fi0 _ le)) f-induction0 p (suc x) le with <-cmp (f (Finduction.pnext I p)) (suc x) ... | tri< a ¬b ¬c = f-induction0 p x (px≤py a) ... | tri≈ ¬a b ¬c = Finduction.ind I (f-induction0 (Finduction.pnext I p) x (y<sx→y≤x f1)) where f1 : f (Finduction.pnext I (Finduction.pnext I p)) < suc x f1 = subst (λ k → f (Finduction.pnext I (Finduction.pnext I p)) < k ) b ( Finduction.decline I {Finduction.pnext I p} (subst (λ k → 0 < k ) (sym b) (s≤s z≤n ) )) ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> le c ) record Ninduction {n m : Level} (P : Set n ) (Q : P → Set m ) (f : P → ℕ) : Set (n Level.⊔ m) where field pnext : (p : P ) → P fzero : {p : P} → f (pnext p) ≡ zero → Q p decline : {p : P} → 0 < f p → f (pnext p) < f p ind : {p : P} → Q (pnext p) → Q p s≤s→≤ : { i j : ℕ} → suc i ≤ suc j → i ≤ j s≤s→≤ = sx≤py→x≤y n-induction : {n m : Level} {P : Set n } → {Q : P → Set m } → (f : P → ℕ) → Ninduction P Q f → (p : P ) → Q p n-induction {n} {m} {P} {Q} f I p = f-induction0 p (f (Ninduction.pnext I p)) ≤-refl where f-induction0 : (p : P) → (x : ℕ) → (f (Ninduction.pnext I p)) ≤ x → Q p f-induction0 p zero lt = Ninduction.fzero I {p} (fi0 _ lt) f-induction0 p (suc x) le with <-cmp (f (Ninduction.pnext I p)) (suc x) ... | tri< a ¬b ¬c = f-induction0 p x (px≤py a) ... | tri≈ ¬a b ¬c = Ninduction.ind I (f-induction0 (Ninduction.pnext I p) x (s≤s→≤ nle) ) where f>0 : 0 < f (Ninduction.pnext I p) f>0 = subst (λ k → 0 < k ) (sym b) ( s≤s z≤n ) nle : suc (f (Ninduction.pnext I (Ninduction.pnext I p))) ≤ suc x nle = subst (λ k → suc (f (Ninduction.pnext I (Ninduction.pnext I p))) ≤ k) b (Ninduction.decline I {Ninduction.pnext I p} f>0 ) ... | tri> ¬a ¬b c = ⊥-elim ( nat-≤> le c ) record Factor (n m : ℕ ) : Set where field factor : ℕ remain : ℕ is-factor : factor * n + remain ≡ m record Factor< (n m : ℕ ) : Set where field factor : ℕ remain : ℕ is-factor : factor * n + remain ≡ m remain<n : remain < n record Dividable (n m : ℕ ) : Set where field factor : ℕ is-factor : factor * n + 0 ≡ m open Factor DtoF : {n m : ℕ} → Dividable n m → Factor n m DtoF {n} {m} record { factor = f ; is-factor = fa } = record { factor = f ; remain = 0 ; is-factor = fa } FtoD : {n m : ℕ} → (fc : Factor n m) → remain fc ≡ 0 → Dividable n m FtoD {n} {m} record { factor = f ; remain = r ; is-factor = fa } refl = record { factor = f ; is-factor = fa } --divdable^2 : ( n k : ℕ ) → Dividable k ( n * n ) → Dividable k n --divdable^2 n k dn2 = {!!} decf : { n k : ℕ } → ( x : Factor k (suc n) ) → Factor k n decf {n} {k} record { factor = f ; remain = r ; is-factor = fa } = decf1 {n} {k} f r fa where decf1 : { n k : ℕ } → (f r : ℕ) → (f * k + r ≡ suc n) → Factor k n decf1 {n} {k} f (suc r) fa = -- this case must be the first record { factor = f ; remain = r ; is-factor = ( begin -- fa : f * k + suc r ≡ suc n f * k + r ≡⟨ cong pred ( begin suc ( f * k + r ) ≡⟨ +-comm _ r ⟩ r + suc (f * k) ≡⟨ sym (+-assoc r 1 _) ⟩ (r + 1) + f * k ≡⟨ cong (λ t → t + f * k ) (+-comm r 1) ⟩ (suc r ) + f * k ≡⟨ +-comm (suc r) _ ⟩ f * k + suc r ≡⟨ fa ⟩ suc n ∎ ) ⟩ n ∎ ) } where open ≡-Reasoning decf1 {n} {zero} (suc f) zero fa = ⊥-elim ( nat-≡< fa ( begin suc (suc f * zero + zero) ≡⟨ cong suc (+-comm _ zero) ⟩ suc (f * 0) ≡⟨ cong suc (*-comm f zero) ⟩ suc zero ≤⟨ s≤s z≤n ⟩ suc n ∎ )) where open ≤-Reasoning decf1 {n} {suc k} (suc f) zero fa = record { factor = f ; remain = k ; is-factor = ( begin -- fa : suc (k + f * suc k + zero) ≡ suc n f * suc k + k ≡⟨ +-comm _ k ⟩ k + f * suc k ≡⟨ +-comm zero _ ⟩ (k + f * suc k) + zero ≡⟨ cong pred fa ⟩ n ∎ ) } where open ≡-Reasoning div0 : {k : ℕ} → Dividable k 0 div0 {k} = record { factor = 0; is-factor = refl } div= : {k : ℕ} → Dividable k k div= {k} = record { factor = 1; is-factor = ( begin k + 0 * k + 0 ≡⟨ trans ( +-comm _ 0) ( +-comm _ 0) ⟩ k ∎ ) } where open ≡-Reasoning div1 : { k : ℕ } → k > 1 → ¬ Dividable k 1 div1 {k} k>1 record { factor = f1 ; is-factor = fa } = ⊥-elim ( nat-≡< (sym fa) ( begin 2 ≤⟨ k>1 ⟩ k ≡⟨ +-comm 0 _ ⟩ k + 0 ≡⟨ refl ⟩ 1 * k ≤⟨ *-mono-≤ {1} {f1} (lem1 _ fa) ≤-refl ⟩ f1 * k ≡⟨ +-comm 0 _ ⟩ f1 * k + 0 ∎ )) where open ≤-Reasoning lem1 : (f1 : ℕ) → f1 * k + 0 ≡ 1 → 1 ≤ f1 lem1 zero () lem1 (suc f1) eq = s≤s z≤n div+div : { i j k : ℕ } → Dividable k i → Dividable k j → Dividable k (i + j) ∧ Dividable k (j + i) div+div {i} {j} {k} di dj = ⟪ div+div1 , subst (λ g → Dividable k g) (+-comm i j) div+div1 ⟫ where fki = Dividable.factor di fkj = Dividable.factor dj div+div1 : Dividable k (i + j) div+div1 = record { factor = fki + fkj ; is-factor = ( begin (fki + fkj) * k + 0 ≡⟨ +-comm _ 0 ⟩ (fki + fkj) * k ≡⟨ *-distribʳ-+ k fki _ ⟩ fki * k + fkj * k ≡⟨ cong₂ ( λ i j → i + j ) (+-comm 0 (fki * k)) (+-comm 0 (fkj * k)) ⟩ (fki * k + 0) + (fkj * k + 0) ≡⟨ cong₂ ( λ i j → i + j ) (Dividable.is-factor di) (Dividable.is-factor dj) ⟩ i + j ∎ ) } where open ≡-Reasoning div-div : { i j k : ℕ } → k > 1 → Dividable k i → Dividable k j → Dividable k (i - j) ∧ Dividable k (j - i) div-div {i} {j} {k} k>1 di dj = ⟪ div-div1 di dj , div-div1 dj di ⟫ where div-div1 : {i j : ℕ } → Dividable k i → Dividable k j → Dividable k (i - j) div-div1 {i} {j} di dj = record { factor = fki - fkj ; is-factor = ( begin (fki - fkj) * k + 0 ≡⟨ +-comm _ 0 ⟩ (fki - fkj) * k ≡⟨ distr-minus-* {fki} {fkj} ⟩ (fki * k) - (fkj * k) ≡⟨ cong₂ ( λ i j → i - j ) (+-comm 0 (fki * k)) (+-comm 0 (fkj * k)) ⟩ (fki * k + 0) - (fkj * k + 0) ≡⟨ cong₂ ( λ i j → i - j ) (Dividable.is-factor di) (Dividable.is-factor dj) ⟩ i - j ∎ ) } where open ≡-Reasoning fki = Dividable.factor di fkj = Dividable.factor dj open _∧_ div+1 : { i k : ℕ } → k > 1 → Dividable k i → ¬ Dividable k (suc i) div+1 {i} {k} k>1 d d1 = div1 k>1 div+11 where div+11 : Dividable k 1 div+11 = subst (λ g → Dividable k g) (minus+y-y {1} {i} ) ( proj2 (div-div k>1 d d1 ) ) div<k : { m k : ℕ } → k > 1 → m > 0 → m < k → ¬ Dividable k m div<k {m} {k} k>1 m>0 m<k d = ⊥-elim ( nat-≤> (div<k1 (Dividable.factor d) (Dividable.is-factor d)) m<k ) where div<k1 : (f : ℕ ) → f * k + 0 ≡ m → k ≤ m div<k1 zero eq = ⊥-elim (nat-≡< eq m>0 ) div<k1 (suc f) eq = begin k ≤⟨ x≤x+y ⟩ k + (f * k + 0) ≡⟨ sym (+-assoc k _ _) ⟩ k + f * k + 0 ≡⟨ eq ⟩ m ∎ where open ≤-Reasoning 0<factor : { m k : ℕ } → k > 0 → m > 0 → (d : Dividable k m ) → Dividable.factor d > 0 0<factor {m} {k} k>0 m>0 d with Dividable.factor d in eq1 ... | zero = ⊥-elim ( nat-≡< ff1 m>0 ) where ff1 : 0 ≡ m ff1 = begin 0 ≡⟨⟩ 0 * k + 0 ≡⟨ cong (λ j → j * k + 0) (sym eq1) ⟩ Dividable.factor d * k + 0 ≡⟨ Dividable.is-factor d ⟩ m ∎ where open ≡-Reasoning ... | suc t = s≤s z≤n div→k≤m : { m k : ℕ } → k > 1 → m > 0 → Dividable k m → m ≥ k div→k≤m {m} {k} k>1 m>0 d with <-cmp m k ... | tri< a ¬b ¬c = ⊥-elim ( div<k k>1 m>0 a d ) ... | tri≈ ¬a refl ¬c = ≤-refl ... | tri> ¬a ¬b c = <to≤ c div1*k+0=k : {k : ℕ } → 1 * k + 0 ≡ k div1*k+0=k {k} = begin 1 * k + 0 ≡⟨ cong (λ g → g + 0) (+-comm _ 0) ⟩ k + 0 ≡⟨ +-comm _ 0 ⟩ k ∎ where open ≡-Reasoning factor< : {k m : ℕ} → k > 1 → Factor< k m factor< {k} {m} k>1 = n-induction {_} {_} {ℕ} {λ m → Factor< k m} F I m where F : ℕ → ℕ F m = m F0 : ( m : ℕ ) → F (m - k) ≡ 0 → Factor< k m F0 0 eq = record { factor = 0 ; remain = 0 ; is-factor = refl ; remain<n = <-trans a<sa k>1 } F0 (suc m) eq with <-cmp k (suc m) ... | tri< a ¬b ¬c = record { factor = 1 ; remain = 0 ; is-factor = lem00 ; remain<n = <-trans a<sa k>1 } where lem00 : k + zero + 0 ≡ suc m lem00 = begin -- minus (suc m) k ≡ 0 k + zero + 0 ≡⟨ +-comm (k + 0) _ ⟩ k + 0 ≡⟨ +-comm k _ ⟩ k ≡⟨ sym ( i-j=0→i=j (≤-trans a≤sa a) eq ) ⟩ suc m ∎ where open ≡-Reasoning ... | tri≈ ¬a b ¬c = record { factor = 1 ; remain = 0 ; is-factor = trans (trans (+-comm (k + 0) _) (+-comm k 0)) b ; remain<n = <-trans a<sa k>1 } ... | tri> ¬a ¬b c = record { factor = 0 ; remain = suc m ; is-factor = refl ; remain<n = c } ind : {m : ℕ} → Factor< k (m - k) → Factor< k m ind {m} record { factor = f ; remain = r ; is-factor = isf ; remain<n = r<n } with <-cmp k (suc m) ... | tri≈ ¬a b ¬c = record { factor = 0 ; remain = m ; is-factor = refl ; remain<n = subst (λ j → m < j) (sym b) a<sa } ... | tri> ¬a ¬b c = record { factor = 0 ; remain = m ; is-factor = refl ; remain<n = <-trans a<sa c } ... | tri< a ¬b ¬c = record { factor = suc f ; remain = r ; is-factor = lem00 ; remain<n = r<n } where k<sm : k < suc m k<sm = a lem00 : k + f * k + r ≡ m lem00 = begin k + f * k + r ≡⟨ +-assoc k _ _ ⟩ k + (f * k + r) ≡⟨ +-comm k _ ⟩ (f * k + r) + k ≡⟨ cong (λ i → i + k ) isf ⟩ (m - k) + k ≡⟨ minus+n k<sm ⟩ m ∎ where open ≡-Reasoning decl : {m : ℕ } → 0 < m → m - k < m decl {m} 0<m = y-x<y (<-trans a<sa k>1 ) 0<m I : Ninduction ℕ _ F I = record { pnext = λ p → p - k ; fzero = λ {m} eq → F0 m eq ; decline = λ {m} lt → decl lt ; ind = λ {p} prev → ind prev } Factor<→¬k≤m : {k m : ℕ} → k ≤ m → (x : Factor< k m ) → Factor<.factor x > 0 Factor<→¬k≤m {k} {m} k≤m x with Factor<.factor x in eqx ... | zero = ⊥-elim ( nat-≤> k≤m (begin suc m ≡⟨ cong suc (sym (Factor<.is-factor x)) ⟩ suc (Factor<.factor x * k + Factor<.remain x) ≡⟨ cong (λ j → suc (j * k + _)) eqx ⟩ suc (0 * k + Factor<.remain x) ≡⟨ refl ⟩ suc (Factor<.remain x) ≤⟨ Factor<.remain<n x ⟩ k ∎ ) ) where open ≤-Reasoning ... | suc fa = s≤s z≤n Factor<-inject : {k m : ℕ} → k > 1 → (x y : Factor< k m) → (Factor<.factor x ≡ Factor<.factor y ) ∧ (Factor<.remain x ≡ Factor<.remain y ) Factor<-inject {k} {m} k>1 x y = n-induction {_} {_} {ℕ} {λ m → (x y : Factor< k m) → (Factor<.factor x ≡ Factor<.factor y ) ∧ (Factor<.remain x ≡ Factor<.remain y ) } F I m x y where F : ℕ → ℕ F m = m f00 : (m : ℕ ) → ( k ≡ suc m ) → (x y : Factor< k (suc m)) → (Factor<.factor x ≡ Factor<.factor y ) ∧ (Factor<.remain x ≡ Factor<.remain y ) f00 m lem00 x y = ⟪ trans (lem02 x) (sym (lem02 y)) , trans (lem01 x) (sym (lem01 y)) ⟫ where lem02 : (f : Factor< k (suc m)) → Factor<.factor f ≡ 1 lem02 f with <-cmp (Factor<.factor f) 1 ... | tri< a ¬b ¬c = ⊥-elim ( nat-≡< (Factor<.is-factor f) (begin suc (Factor<.factor f * k + Factor<.remain f) ≤⟨ s≤s (≤-plus {_} {_} {Factor<.remain f} (*≤ (px≤py a)) ) ⟩ suc (0 * k + Factor<.remain f) ≡⟨⟩ suc (0 + Factor<.remain f) ≡⟨⟩ suc (Factor<.remain f) ≤⟨ Factor<.remain<n f ⟩ k ≡⟨ lem00 ⟩ suc m ∎ )) where open ≤-Reasoning ... | tri≈ ¬a b ¬c = b ... | tri> ¬a ¬b c = ⊥-elim ( nat-≡< (sym (Factor<.is-factor f)) (begin -- 1 < Factor<. factor f, fa * k + r > k ≡ suc m suc (suc m) ≡⟨ cong suc (sym lem00) ⟩ suc k ≡⟨ sym (+-comm k 1) ⟩ k + 1 <⟨ <-plus-0 k>1 ⟩ k + k ≡⟨ cong (λ j → k + j) (+-comm 0 _ ) ⟩ k + (k + 0) ≡⟨⟩ k + (k + 0 * k) ≡⟨ refl ⟩ 2 * k ≤⟨ *≤ c ⟩ Factor<.factor f * k ≤⟨ x≤x+y ⟩ Factor<.factor f * k + Factor<.remain f ∎ ) ) where open ≤-Reasoning lem03 : k ≡ 1 * k lem03 = +-comm 0 k lem01 : (f : Factor< k (suc m)) → Factor<.remain f ≡ 0 lem01 f = +-cancel-1 _ _ _ ( begin Factor<.factor f * k + Factor<.remain f ≡⟨ Factor<.is-factor f ⟩ suc m ≡⟨ sym lem00 ⟩ k ≡⟨ +-comm 0 k ⟩ k + 0 ≡⟨ cong (λ j → j + 0) lem03 ⟩ 1 * k + 0 ≡⟨ cong (λ j → j * k + 0) (sym (lem02 f)) ⟩ Factor<.factor f * k + 0 ∎ ) where open ≡-Reasoning F0 : ( m : ℕ ) → F (m - k) ≡ 0 → (x y : Factor< k m) → (Factor<.factor x ≡ Factor<.factor y ) ∧ (Factor<.remain x ≡ Factor<.remain y ) F0 0 eq x y = ⟪ trans (lem00 x) (sym (lem00 y)) , trans (lem01 x) (sym (lem01 y)) ⟫ where lem01 : (f : Factor< k 0) → Factor<.remain f ≡ 0 lem01 f with Factor<.remain f in eq1 ... | zero = refl ... | suc n = ⊥-elim ( nat-≡< (sym (Factor<.is-factor f)) (begin suc 0 ≤⟨ s≤s z≤n ⟩ suc n ≡⟨ sym eq1 ⟩ Factor<.remain f ≡⟨ refl ⟩ 0 + Factor<.remain f ≤⟨ x≤y+x ⟩ Factor<.factor f * k + Factor<.remain f ∎ ) ) where open ≤-Reasoning lem00 : (f : Factor< k 0) → Factor<.factor f ≡ 0 lem00 f with m*n=0⇒m=0∨n=0 {Factor<.factor f} {k} (trans (+-comm 0 (Factor<.factor f * k) ) (subst (λ j → _ + j ≡ 0) (lem01 f) (Factor<.is-factor f))) ... | case1 fa=0 = fa=0 ... | case2 k=0 = ⊥-elim (nat-≡< (sym k=0) (<-trans a<sa k>1) ) F0 (suc m) eq x y with <-cmp k (suc m) ... | tri< a ¬b ¬c = ⊥-elim ( ¬b lem00 ) where lem00 : k ≡ suc m lem00 = begin k ≡⟨ sym ( i-j=0→i=j (≤-trans a≤sa a) eq ) ⟩ suc m ∎ where open ≡-Reasoning ... | tri≈ ¬a b ¬c = f00 m b x y ... | tri> ¬a ¬b c = ⟪ trans ( lem00 x ) (sym (lem00 y)) , trans (lem01 x) (sym (lem01 y)) ⟫ where lem00 : (f : Factor< k (suc m)) → Factor<.factor f ≡ 0 lem00 f with Factor<.factor f in eq1 ... | zero = refl ... | suc fa = ⊥-elim ( nat-≡< (sym (Factor<.is-factor f)) (begin suc (suc m) ≤⟨ c ⟩ k ≤⟨ x≤x+y ⟩ k + Factor<.remain f ≡⟨ cong (λ j → j + _) (+-comm 0 k) ⟩ suc 0 * k + Factor<.remain f ≤⟨ ≤-plus {_} {_} {Factor<.remain f} (*≤ {suc 0} {suc fa} {k} (s≤s z≤n)) ⟩ suc fa * k + Factor<.remain f ≡⟨ cong (λ j → j * k + Factor<.remain f) (sym eq1) ⟩ Factor<.factor f * k + Factor<.remain f ∎ ) ) where open ≤-Reasoning lem01 : (f : Factor< k (suc m)) → Factor<.remain f ≡ (suc m) lem01 f = begin Factor<.remain f ≡⟨ refl ⟩ 0 * k + Factor<.remain f ≡⟨ cong (λ j → j * k + Factor<.remain f) (sym (lem00 f)) ⟩ Factor<.factor f * k + Factor<.remain f ≡⟨ Factor<.is-factor f ⟩ suc m ∎ where open ≡-Reasoning ind : {m : ℕ} → ( (x y : Factor< k (m - k)) → (Factor<.factor x ≡ Factor<.factor y ) ∧ (Factor<.remain x ≡ Factor<.remain y ) ) → (x y : Factor< k m) → (Factor<.factor x ≡ Factor<.factor y ) ∧ (Factor<.remain x ≡ Factor<.remain y ) ind {m} prev x y with <∨≤ m k ... | case1 m<k = ⟪ trans (lem00 x) (sym (lem00 y)) , trans (lem01 x) (sym (lem01 y)) ⟫ where lem00 : (x : Factor< k m ) → Factor<.factor x ≡ 0 lem00 x with Factor<.factor x in eqx ... | zero = refl ... | suc fa = ⊥-elim ( nat-≤> (begin k ≤⟨ x≤x+y ⟩ k + (fa * k + Factor<.remain x) ≡⟨ sym (+-assoc k _ _) ⟩ ( k + fa * k ) + Factor<.remain x ≡⟨ refl ⟩ suc fa * k + Factor<.remain x ≡⟨ cong (λ j → j * k + Factor<.remain x) (sym eqx) ⟩ Factor<.factor x * k + Factor<.remain x ≡⟨ Factor<.is-factor x ⟩ m ∎ ) m<k ) where open ≤-Reasoning lem01 : (f : Factor< k m) → Factor<.remain f ≡ m lem01 f = begin Factor<.remain f ≡⟨ refl ⟩ 0 * k + Factor<.remain f ≡⟨ cong (λ j → j * k + Factor<.remain f) (sym (lem00 f)) ⟩ Factor<.factor f * k + Factor<.remain f ≡⟨ Factor<.is-factor f ⟩ m ∎ where open ≡-Reasoning ... | case2 k≤m = px=py x y k≤m where lem07 : (x : Factor< k m ) → {fa : ℕ } → suc fa ≡ Factor<.factor x → fa * k + Factor<.remain x ≡ m - k lem07 x {fa} eq1 = begin fa * k + Factor<.remain x ≡⟨ sym (minus+y-y {_} {k} ) ⟩ (fa * k + Factor<.remain x + k ) - k ≡⟨ cong (λ j → j - k) ( begin fa * k + Factor<.remain x + k ≡⟨ +-assoc (fa * k) _ _ ⟩ fa * k + (Factor<.remain x + k) ≡⟨ cong (λ j → fa * k + j) (+-comm _ k) ⟩ fa * k + (k + Factor<.remain x ) ≡⟨ sym (+-assoc (fa * k) k _ ) ⟩ (fa * k + k) + Factor<.remain x ≡⟨ cong (λ j → j + Factor<.remain x ) (+-comm (fa * k) k) ⟩ suc fa * k + Factor<.remain x ≡⟨ cong (λ j → j * k + _) (eq1) ⟩ Factor<.factor x * k + Factor<.remain x ∎ ) ⟩ (Factor<.factor x * k + Factor<.remain x) - k ≡⟨ cong (λ j → j - k ) (Factor<.is-factor x) ⟩ m - k ∎ where open ≡-Reasoning px=py : (x y : Factor< k m) → k ≤ m → (Factor<.factor x ≡ Factor<.factor y ) ∧ (Factor<.remain x ≡ Factor<.remain y ) px=py x y k≤m with Factor<.factor x in eqx | Factor<.factor y in eqy ... | zero | _ = ⊥-elim ( nat-≡< (sym eqx) (Factor<→¬k≤m k≤m x) ) ... | _ | zero = ⊥-elim ( nat-≡< (sym eqy) (Factor<→¬k≤m k≤m y) ) ... | suc fx | suc fy with prev record { factor = fx ; remain = Factor<.remain x ; is-factor = lem07 x (sym eqx) ; remain<n = Factor<.remain<n x } record { factor = fy ; remain = Factor<.remain y ; is-factor = lem07 y (sym eqy) ; remain<n = Factor<.remain<n y } ... | ⟪ eqf , eqr ⟫ = ⟪ cong suc eqf , eqr ⟫ decl : {m : ℕ } → 0 < m → m - k < m decl {m} 0<m = y-x<y (<-trans a<sa k>1 ) 0<m I : Ninduction ℕ _ F I = record { pnext = λ p → p - k ; fzero = λ {m} eq → F0 m eq ; decline = λ {m} lt → decl lt ; ind = λ {p} prev → ind prev } F<toD : {n m : ℕ} → (fc : Factor< n m) → Factor<.remain fc ≡ 0 → Dividable n m F<toD {n} {m} record { factor = f ; remain = r ; is-factor = fa ; remain<n = _ } refl = record { factor = f ; is-factor = fa } DtoF< : {n m : ℕ} → Dividable n m → 0 < n → Factor< n m DtoF< {n} {m} record { factor = f ; is-factor = fa } 0<n = record { factor = f ; is-factor = fa ; remain = 0 ; remain<n = 0<n } F<to¬D : {n m nx : ℕ} → (fc : Factor< n m) → 1 < n → Factor<.remain fc ≡ suc nx → ¬ Dividable n m F<to¬D {n} {m} fc 1<n eq div = ⊥-elim ( nat-≡< (sym (proj2 ( Factor<-inject {n} {m} 1<n fc (DtoF< div (<-trans a<sa 1<n) )))) 0<r ) where 0<r : 0 < Factor<.remain fc 0<r = subst ( λ k → 0 < k ) (sym eq) (s≤s z≤n) -- -- we can use factor< and check Factor.remain ≡ 0 -- Factor.remain ≡ 0 → Dividable k m -- ¬ Factor.remain ≡ 0 → ¬ Dividable k m -- decD : {k m : ℕ} → k > 1 → Dec0 (Dividable k m ) decD {k} {m} k>1 = dec0 (factor< {k} {m} k>1) where dec0 : Factor< k m → Dec0 (Dividable k m) dec0 fc with Factor<.remain fc in eq1 ... | zero = yes0 record { factor = Factor<.factor fc ; is-factor = trans (cong (λ j → Factor<.factor fc * k + j) (sym eq1)) (Factor<.is-factor fc) } ... | suc t = no0 ( λ dv → F<to¬D fc k>1 eq1 dv )